2013
DOI: 10.1364/ol.38.000344
|View full text |Cite
|
Sign up to set email alerts
|

Tunable photonic microwave generation using optically injected semiconductor laser dynamics with optical feedback stabilization

Abstract: The period-one (P1) nonlinear dynamics of a semiconductor laser subject to both optical injection and optical feedback are investigated for photonic microwave generation. The optical injection first drives the laser into P1 dynamics so that its intensity oscillates at a microwave frequency. A dual-loop optical feedback then stabilizes the fluctuations of the oscillation frequency. Photonic generation at 45.424 GHz is demonstrated with a linewidth below 50 kHz using a laser with a relaxation resonance frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 18 publications
5
75
0
Order By: Relevance
“…Here in contrast we have demonstrated that the fundamental resonance frequency in the optically injected laser can be made insensitive to fluctuations in the laser current and operating temperature so that it is only sensitive to the amplitude of the injected optical signal from the master laser. This leads to the second interesting aspect of this paper: Photonic oscillators have been proposed for a variety of applications and the discovery of these operating points shows that the optically injected laser may be able to display favorable phase noise and jitter characteristics to go along with its wide tuning range [21], [24]. Potentially, these operating points can be complemented by other nonlinear dynamics noise reduction techniques such as those recently implemented in nanomechanical oscillators [39].…”
Section: Results: Experimental Measurements and Numerical Simulatmentioning
confidence: 99%
See 2 more Smart Citations
“…Here in contrast we have demonstrated that the fundamental resonance frequency in the optically injected laser can be made insensitive to fluctuations in the laser current and operating temperature so that it is only sensitive to the amplitude of the injected optical signal from the master laser. This leads to the second interesting aspect of this paper: Photonic oscillators have been proposed for a variety of applications and the discovery of these operating points shows that the optically injected laser may be able to display favorable phase noise and jitter characteristics to go along with its wide tuning range [21], [24]. Potentially, these operating points can be complemented by other nonlinear dynamics noise reduction techniques such as those recently implemented in nanomechanical oscillators [39].…”
Section: Results: Experimental Measurements and Numerical Simulatmentioning
confidence: 99%
“…ject to injected optical signals has received considerable attention as a tool for the characterization of the intrinsic dynamic parameters of semiconductor lasers [4]- [8], and as a mechanism for enhancing the fundamental modulation characteristics [9]- [12], with applications in communications [13]- [16], RADAR [17], LIDAR [18], cryptography [19], random bit generation [20], and photonic frequency synthesis [21]- [24]. Under external injection, the semiconductor laser can be induced to display a broad range of output characteristics including stable injection locking, periodic power oscillations at the fundamental dynamic resonance frequency of the system and its subharmonics, and chaotic dynamics [25]- [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for a certain range of optical feedback levels, SLs may behave unstable oscillations including P1, multi-periodic oscillation (MP), and CO [13][14][15][16][17]. Especially, in many particular application fields, both the optical injection and optical feedback may be needed to introduce into SLs simultaneously [18][19][20][21][22]. For examples, in some applications related to narrow linewidth microwave photonic signals, optical feedback is used to stabilize the oscillation frequency of microwave photonic signals generated by a SL under optical injection [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, in many particular application fields, both the optical injection and optical feedback may be needed to introduce into SLs simultaneously [18][19][20][21][22]. For examples, in some applications related to narrow linewidth microwave photonic signals, optical feedback is used to stabilize the oscillation frequency of microwave photonic signals generated by a SL under optical injection [18][19][20]. In some applications requiring broad bandwidth chaos signals, optical injection is adopted to enhance the bandwidth of the chaos generated by a SL with optical feedback [21][22][23].…”
Section: Introductionmentioning
confidence: 99%